Effect of sodium-alginate and laminaran on Salmonella Typhimurium infection in human enterocyte-like HT-29-Luc cells and BALB/c mice. (10th July 2015) - Kuda, Takashi; Kosaka, Misa; Hirano, Shino; Kawahara, Miho; Sato, Masahiro; Kaneshima, Tai; Nishizawa, Makoto; Takahashi, Hajime; Kimura, Bon
Highlights: Both alginate and laminaran are brown algal polysaccharides. Laminaran can be easily fermented by intestinal microbiota. The alginate and laminaran inhibited Salmonella and Listeria invasion in HT-29 cells. 2% Na-alginate diet suppressed S . Typhimurium infection in BALB/c mice. On the other hand, laminaran could not inhibit the infection. Abstract: Brown algal polysaccharides such as alginate, polymers of uronic acids, and laminaran, beta-1, 3 and 1, 6-glucan, can be fermented by human intestinal microbiota. To evaluate the effects of these polysaccharides on infections caused by food poisoning pathogens, we investigated the adhesion and invasion of pathogens ( Salmonella Typhimurium, Listeria monocytogenes and Vibrio parahaemolyticus ) in human enterocyte-like HT-29-Luc cells and in infections caused in BALB/c mice. Both sodium Na-alginate and laminaran (0.1% each) inhibited the adhesion of the pathogens to HT-29-Luc cells by approximately 70–90%. The invasion of S . Typhimurium was also inhibited by approximately 70 and 80% by Na-alginate and laminaran, respectively. We observed that incubation with Na-alginate for 18 h increased the transepithelial electrical resistance of HT-29-Luc monolayer cells. Four days after inoculation with 7 log CFU/mouse of S . Typhimurium, the faecal pathogen count in mice that were not fed polysaccharides (control mice) was about 6.5 log CFU/g while the count in mice that were fed Na-alginate had decreased to 5.0 log CFU/g. The liver pathogen count, which was 4.1 log CFU/g in the control mice, was also decreased in mice that were fed Na-alginate. In contrast, the mice that were fed laminaran exhibited a more severe infection than that exhibited by control mice.